2020
DOI: 10.1155/2020/4938161
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Sports Behavior and Social Networks: The Role of Social Efficacy and Self-Presentation in Sports Behavior

Abstract: Social networks are a complex system that members communicate, create new connections or destroy existing connections, and further deliver major impacts on each member’s life. Given the spread of the Internet and increased academic pressure, sedentary and prescreen behaviors are very common among adolescents; meanwhile, sports behaviors are gradually decreasing. This situation has had an adverse effect on health. This paper used a questionnaire survey to investigate the influence of social networks on adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(22 reference statements)
0
2
1
Order By: Relevance
“…On the other hand, perceived behavioral control has a positive effect on fitness intention. It is not different from Banerjee and Ho (2019) and Lee et al.’s (2020)Lee et al. 2020 findings.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…On the other hand, perceived behavioral control has a positive effect on fitness intention. It is not different from Banerjee and Ho (2019) and Lee et al.’s (2020)Lee et al. 2020 findings.…”
Section: Resultscontrasting
confidence: 56%
“…, 2019a, b), etc. A study has confirmed that individual's cognition can influence behavioral choice (Lei et al , 2020). People generally participate in physical activities to meet the needs of physical interests, mental health, challenges.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation